Mechanism and Complex Roles of HSC70 in Viral Infections - Wang, Zeng; Li, Yongtao; Yang, Xia; Zhao, Jun; Cheng, Yuening; Wang, Jianke (Frontiers in Microbiology, 2020)
Heat shock cognate 71 kDa protein (HSC70), a constitutively expressed molecular chaperon within the heat shock protein 70 family, plays crucial roles in maintaining cellular environmental homeostasis through implicating in a wide variety of physiological processes, such as ATP metabolism, protein folding and transporting, antigen processing and presentation, endocytosis, and autophagy. Notably, HSC70 also participates in multiple non-communicable diseases and some pathogen-caused infectious diseases. It’s known that virus is an obligatory intracellular parasite and heavily relies on host machineries to self-replication. Undoubtedly, HSC70 is a striking target manipulated by virus to ensure the successful propagation. In this review, we summarize the recent advances of the regulatory mechanisms of HSC70 during viral infections, which will be conducive to further study viral pathogenesis.